PENGARUH IBU HAMIL PEROKOK PASIF TERHADAP KEJADIAN LAHIR MATI DI KOTA AMBON - Magdalena Paunno; Ova Emilia; Abdul Wahab (JURNAL KESEHATAN REPRODUKSI, 2016)
PENGARUH IBU HAMIL PEROKOK PASIF TERHADAPKEJADIAN LAHIR MATI DI KOTA AMBONMagdalena Paunno1, Ova Emillia2, Abdul Wahab3ABSTRACTBackground: Intervention in the care for pregnant women can reduce antenatal mortality until 75%.Antenatal Care (ANC) in Ambon municipality is categorized good if compared from the mean rate ofnational level, that is, Visit 1 (89%) and Visit 4 (87.76%); however, the incidence of stillbirths in Ambonis still considered high. Data about the incidence of stillbirths in three hospitals of Ambon showed thatthere were 44.2 stillbirths per 1000 live births while national data in 2003 showed that there were only9.6 stillbirths per 1000 live births. The direct cause of stillbirth is hypoxia, that is, the lack of oxygenin a pregnant woman’s body due to the exposure of cigarette smoke. In Ambon municipality, 65% ofhouseholds have 1 active smoker and almost all of the smokers (90%) smoke inside the house. This rateof course exceeds the national rate. In addition, other factors causing stillbirth are the quality of antenatalcare, age, parity, anemia and women’s educational level.Objective: To study whether passive smoking during pregnancy is a risk factor of the incidence of stillbirths.Method: This was an observational study with case-control study design. Study sites were in three hospitalsof Ambon municipality, namely Dr. M. Haulussy District Hospital, Al-Fatah Hospital, and Sumber HidupHospital. Subjects were divided into two groups which were case and control with comparison of 1:1 (69stillbirths as case and 69 live births as control) from January to December 2007. Samples were taken usingnon probability sampling which was determined with quota sample. The analysis of quantitative dataused univariable analysis, bivariable analysis with chi-square test (χ²) and stratification, and multivariableanalysis with logistic regression.Result and Discussion: There was a significant relationship between passive smoking during pregnancyand the incidence of stillbirth based on bivariable analysis with OR=3.36 (95% CI=1.20-5.41) while basedon multivariable analysis with OR=2.8 (1.01-7.94). Other risk factors that affected the incidence of stillbirthwere the quality of antenatal care with OR=3.2 (95% CI=1.39-7.52) and anemia during pregnancy withOR=2.3 (95% CI=1.20-5.41). Meanwhile, stratification analysis showed that non anemic women duringpregnancy was significantly related to stillbirths with OR=5.7 (95% CI 1.10-55.22). However, age, parity andeducation were not the risk factors of the incidence of stillbirth in Ambon.Conclusion: Passive smoking during pregnancy was a risk factor of the incidence of stillbirth in Ambonmunicipality. Other factors that caused the incidence of stillbirths were the quality of antenatal care andanemia. However, age, and parity were not the risk factors of the incidence of stillbirths in Ambon.Keywords: pregnant woman, passive smoking, stillbirthINTISARILatar belakang: Intervensi pada perawatan ibu hamil dapat menurunkan kematian perinatal hingga 75%.ANC di Kota Ambon dikategorikan baik, bila dilihat angka rata-rata secara nasional yaitu K1 89%, K4 87,76%namun, kejadian lahir mati sangat tinggi dibanding angka nasional. Salah satu penyebab langsung lahirmati adalah hypokxia yaitu kekurangan oksigen dalam tubuh ibu, akibat dari ibu hamil terpapar asaprokok. Di Kota Ambon, 65% rumah tangga mempunyai 1 orang perokok, dan hampir semua perokok (90%)merokok di rumah. Angka ini lebih tinggi dari angka nasional. Faktor lain menyebabkan lahir mati adalahkualitas antenatal care, umur, paritas anemia ibu selama hamil, pendidikan ibu yang rendah.Tujuan: Penelitian ini untuk mengetahui apakah ibu hamil perokok pasif merupakan faktor risiko kejadianlahir mati.Metode: Penelitian observasional dengan rancangan kasus-kontrol. Lokasi penelitian pada 3 RS di KotaAmbon yaitu: RSUD dr. M. Haulussy, RS. Al-Fatah, RS. Sumber Hidup. Subjek penelitian 1:1 69 lahir mati(kasus) dan 69 lahir hidup (kontrol) pada bulan Januari sampai dengan bulan Desember 2007. Pengambilansampel dengan cara non probability sampling, ditentukan secara quota sample . Analisis data terdiridari analisis univariabel, analisis bivariabel menggunakan uji chi-square (χ²), stratifikasi serta analisismultivariabel menggunakan regresi logistik.Hasil dan Pembahasan: Ada hubungan yang bermakna antara ibu hamil perokok pasif dengan kejadianlahir mati. Analisis bivariabel OR=3,36 (95% CI=1,20-5,41) analisis multivariabel OR=2,8 (1,01-7,94). Faktorrisiko lain yang mempengaruhi kejadian lahir mati adalah: Kualitas antenatal care mempunyai nilai OR=3,2(95% CI=1,39-7,52), ibu hamil anemia OR=2,3 (95% CI=1,20-5,41) dan pendidikan OR=2,42 ( 1,15-5,10).Saat analisis strativikasi, ibu tidak anemia mempunyai hubungan bermakna dengan lahir mati OR=5,7 (95%CI 1,10-55,22). Umur, paritas dan pendidikan bukan merupakan faktor risiko lahir mati di Kota Ambon.Kesimpulan : Ibu hamil perokok pasif merupakan faktor risiko terhadap kejadian lahir mati di Kota Ambon.Faktor lain yang menyebabkan lahir mati adalah kualitas antenatal care dan anemia ibu hamil.Kata kunci: ibu hamil, perokok pasif, lahir mati.1 Air Selobar Community Health Center, Ambon Health Office, Maluku Province2 Obstetric and Gynecology Division, Faculty of Medicine,Gadjah Mada University, Yogyakarta3 Maternal and Child Health-Reproductive Health, Graduate Program,Faculty of Medicine, Gadjah Mada University, Yogyakarta